Soil organic carbon monitoring in an irrigated agriculture area - Minhoni, Renata Teixeira De Almeida [UNESP] (2021)
There is a global growing interest in agricultural practices to increase soil organic carbon (SOC) to promote soil fertility, climate change mitigation, and food security. Therefore, SOC measuring and monitoring is a key step in agricultural and environmental projects. The first chapter of this study aimed to identify potential proxies for topsoil SOC in an agricultural area, characterized by the adoption of central pivot irrigation, reduced cultivation, crop rotation, and use of crop residues. Nine spectral indices were extracted from time-series Sentinel-2 satellite images of bare soil. Additionally, three topographic indicators were extracted from a digital elevation model (DEM). Linear regression models were generated between the spectral indexes and SOC, considering the soil sampled in 2019, and between topographic indicators and SOC. The spectral indices with the best performance were EVI2 (Enhanced Vegetation Index), NDVI (Normalized Difference Vegetation Index), MSAVI2 (Modified Soil-Adjusted Vegetation Index), and RVI (Ratio Vegetation Index), and the elevation was the best topographic indicator. After a seven-year study period (from 2012 to 2019), the area showed a significant increase in the topsoil SOC. The results of this research consolidate that the use of a multitemporal dataset can lead to more accurate identification of topsoil SOC proxies, instead of the use of a single date image. Two orchards were selected in the region of San Joaquin Valley, California (USA), having as the main objective of the second chapter characterize the multi-scale (tree scale and orchard scale) distribution of SOC and soil total nitrogen (STN) in micro-irrigated citrus orchards, grown under the same soil conservation practice. The first with Page mandarin (Citrus reticulata) in Strathmore, and the second with Washington navel orange (Citrus sinensis) in Ivanhoe. Both orchards are irrigated with micro-sprinklers, and pruning residues are disposed on the inter-rows. Soil samples were collected along transects, and each transect was divided into three sections: the first (α) located 0.6 m from the tree trunk, the second (β) 1.2 m from the trunk (approximately below the canopy projection), and the third (γ) located in the center of the inter-row. In each section single samples were collected at two soil layers, 0-0.05 m and 0.05-0.4 m. From 0 to 0.05 m in Strathmore, the average SOC concentrations in the β and γ sections and the STN concentration in the γ section showed no statistical difference with the orchard. Whereas, from 0.05 to 0.40 m and from 0 to 0.40 m there was no statistical difference between the sections and the orchard. In Ivanhoe, where the soil is more homogeneous, there was no significant difference between the sections and the orchard. The results of this study can support the elaboration of future SOC and STN monitoring projects in the region.